2021
DOI: 10.3892/or.2021.8182
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic pancreatic cancer: Mechanisms and detection (Review)

Abstract: Pancreatic cancer (PC) is a lethal malignancy. Its prevalence rate remains low but continues to grow each year. Among all stages of PC, metastatic PC is defined as late-stage (stage IV) PC and has an even higher fatality rate. Patients with PC do not have any specific clinical manifestations. Most cases are inoperable at the time-point of diagnosis. Prognosis is also poor even with curative-intent surgery. Complications during surgery, postoperative pancreatic fistula and recurrence with metastatic foci make t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 133 publications
0
5
0
Order By: Relevance
“…Pancreatic cancer is one of the malignant tumors of the digestive system with the highest mortality, accounting for the fourth place in the cancer-related mortality [ 1 , 2 ]. In recent years, epidemiology has found that the number of new pancreatic cancer cases in both male and female is increasing [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pancreatic cancer is one of the malignant tumors of the digestive system with the highest mortality, accounting for the fourth place in the cancer-related mortality [ 1 , 2 ]. In recent years, epidemiology has found that the number of new pancreatic cancer cases in both male and female is increasing [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the research revealed a positive correlation between the growth of CTC clusters, consisting of platelets, macrophages, and fibroblasts, and the progression of cancer [ 119 ]. In addition to playing a pivotal role in the metastatic process, blood platelets are also implicated in the acquisition of drug resistance in pancreatic cancer and the fibrosis process of the disease [ 120 , 121 , 122 , 123 ]. The high thrombotic risk in cancer patients is due to the activation and stimulation of platelets to aggregation by CTCs.…”
Section: Discussionmentioning
confidence: 99%
“…The present study used a patient-derived pancreatic cancer liver metastasis to demonstrate the labeling of human metastatic pancreatic cancer, a very important tumor site for fluorescence-guided surgery, as well as the identification of such lesions during staging laparoscopy. In addition to the unique challenges of fluorescence imaging in the liver, metastatic pancreatic tumors have notable changes from their primary site: namely their microenvironment, acquired mutations, and the epithelial–mesenchymal transition [ 27 , 28 ]. Previous studies have shown the ability of fluorescence imaging to detect metastatic colorectal tumors at their site of metastasis, but this has not been attempted with metastatic pancreatic cancer [ 6 , 8 , 29 ].…”
Section: Discussionmentioning
confidence: 99%